Potential sites for waste-bins by using GIS-AHP / Mohamad Khairul Izzudin Saidi and Nabilah Naharudin - Saidi, Mohamad Khairul Izzudin; Naharudin, Nabilah (College of Built Environment, 2023)
Rapid urbanization, population growth and economic development have resulted in increased waste generation in countries across the world.